2020
DOI: 10.5811/cpcem.2020.7.48421
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism Presenting as an Anterior ST-elevation Myocardial Infarction: A Case Report

Abstract: Introduction: While the electrocardiogram (ECG) for pulmonary embolism typically shows tachycardia or evidence of right heart strain, it can demonstrate ischemic changes similar to acute coronary syndrome. Case Report: The patient in this case presented with syncope, chest pain, and an ECG showing an anterior acute myocardial infarction (AMI) without evidence of right heart strain. His cardiac catheterization showed no coronary artery occlusions, but some signs of pulmonary embolism (PE), which was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Higher right ventricular pressure and depressed cardiac output cause coronary hypoperfusion followed by right ventricular myocardial infarction. [8][9][10][11][12][13][14] Our patient was a man in his early 70 s whose ECG showed ST-segment elevation (by approximately 0.1-0.4 mV) in leads V1 to V3 with an upward T-wave, and the postoperative ECG showed that the ST-segment in leads V1-V3 had fallen back with inversion of the T-wave. Three days later, the inversion amplitude of the T-waves in leads V1 to V3 was reduced (Figure 6).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Higher right ventricular pressure and depressed cardiac output cause coronary hypoperfusion followed by right ventricular myocardial infarction. [8][9][10][11][12][13][14] Our patient was a man in his early 70 s whose ECG showed ST-segment elevation (by approximately 0.1-0.4 mV) in leads V1 to V3 with an upward T-wave, and the postoperative ECG showed that the ST-segment in leads V1-V3 had fallen back with inversion of the T-wave. Three days later, the inversion amplitude of the T-waves in leads V1 to V3 was reduced (Figure 6).…”
Section: Discussionmentioning
confidence: 84%
“…Higher right ventricular pressure and depressed cardiac output cause coronary hypoperfusion followed by right ventricular myocardial infarction. 8 14 …”
Section: Discussionmentioning
confidence: 99%
“…17) There are few case reports in literature confirming the presence of STE in patients with a final diagnosis of APE. [19][20][21] Despite the fact that especially in cancer patients and ST deviation in ECG, we always should take APE into account in differential diagnosis on admission, the direct infiltration into LAD appears to be the main reason of such an unexpected clinical presentation in that case. Suga, et al presented a similar case of a YOUNG WOMAN WITH METAPLASTIC BREAST CARCINOMA 73-year-old woman who was admitted to the hospital with the initial diagnosis of STEMI and who was observed fast recurrence of ST segment elevation after balloon angioplasty and initial ECG normalization.…”
Section: Discussionmentioning
confidence: 90%
“…PE can cause a large number of EKG changes. The most common of these is sinus tachycardia; however, incomplete or complete right bundle branch block, atrial dysrhythmias, rightward QRS shift, S1Q3T3, acute pulmonary p-wave, T-wave inversion in the right precordial leads, and an anterior ischemic pattern described as inverted T waves in the precordium or ST-elevation have all been described in the literature [ 5 - 8 ]. The anterior ischemic pattern, in conjunction with initial symptoms that can mimic STEMI, presents a diagnostic conundrum to the emergency physician considering CCL activation.…”
Section: Discussionmentioning
confidence: 99%